Correlation between referral type (emergency vs scheduled) and maternal perinatal outcome in suspected placenta accreta spectrum : a retrospective cohort study in Dr.Kariadi hospital Semarang 2020-2023 - Umami, Hayyina Maslikhatul; Cahyanti , Ratnasari Dwi; Tjahjanto, Hary; Hadijono, Soerjo; Dewantiningrum, Julian; Putra, Very Great Eka (Medica Hospitalia : Journal of Clinical Medicine, 2026)
BACKGROUND : Maternal Mortality Rate (MMR) in Indonesia at 2023 was 189 over 100.000 live births. The most popular reason for maternal death was obstetrics hemorrhage. Obstetric hemorrhage can be caused by abnormal placentation. Abdominal delivery by cesarean section has increased recently in Indonesia. Cesarean section will increase the risk for placenta accreta spectrum, which raises maternal morbidity and mortality. AIM : To analyze the correlation of emergency and scheduled referral with maternal and perinatal outcomes of suspected placenta accreta spectrum patients in Dr.Kariadi Hospital Semarang 2020 – 2023.METHODS : A cohort retrospective study performed in May 2024, involved 153 women with suspected placenta accreta spectrum were referred to Dr.Kariadi Hospital Semarang in 2020 – 2023, divided by emergency referral and scheduled referral groups. We use Placenta Accreta Index (PAI) Score and all patients who fulfilled the criteria of the placenta accreta spectrum based on FIGO to predict suspicious placenta accreta spectrum. Descriptive analysis included the base characteristics of the patients. Correlation analysis with maternal and perinatal outcomes using Chi Square analyze of SPSS 25.00 version.RESULTS : A total of 69 patients with emergency referrals and 84 patients with scheduled referrals. Mean age was 32.97, median 32(24-44), median of gestation was 3(1-6) and 3(1-9), median of gestational age was 35(22-41) and 36(32-39). The emergency referral had a higher risk for cesarean hysterectomy with OR (95%CI) 2.92 (1.51–5.67), for maternal hemorrhage with OR (95%CI) 2.34 (1.22–4.49), for blood transfusion with OR (95%CI) 6.02 (2.46–14.76), for intensive care admission with OR (95%CI) 4.39 (1.5–12.79), for prematurity with OR (95%CI) 2.56(1.32–4.92), for asphyxia with OR (95%CI) 3.41(1.56–7.47). There were significant differences between emergency and scheduled referrals for vaginal delivery (p=0.03), and perinatal mortality (p=0.04). Estimated blood loss was 1453.7± 1253.6 ml in emergency referral and 878.3 ± 823.7 ml in scheduled referral.CONCLUSION : Emergency referrals had worse maternal and perinatal outcomes than scheduled referrals for suspicious placenta accreta spectrum patients.